Disability and community - Carey, Allison C.; Scotch, Richard K., 1951- (Bingley, U.K. : Emerald, 2011)
This volume of Research in Social Science and Disability brings together interdisciplinary scholarship to examine a wide array of issues related to disability and community, a topic of critical importance academically and politically. The evolving and politically contested notions of community sit at the centre of much of the recent research on disability and, as researchers both create and reflect various ideas of membership when defining 'disability' and aggregating individuals, their methodological decisions have significant implications for how we come to understand disability and community. This volume examines a wide range of social institutions and practices such as education, employment, and cultural venues and the extent to which and how they include people with disabilities in the workings of these institutions. It includes research framed by a variety of theoretical perspectives and research methodologies and offers innovative ways to envision inclusive communities and, therefore, enables us to consider how to move forward to create them.
Introduction : disability and community / Richard K. Scotch -- Bowling together : foundations of community among youth with disabilities / Valerie Leiter -- The student body : the intersection of spatial design, architecture, and cultural policy in university communities / Stephen Gilson, Elizabeth DePoy -- Families of children with autism and developmental disabilities : a description of their community interaction / Preethy S. Samuel, Karen L. Hobden, Barbara W. LeRoy -- Building pediatric multiple sclerosis community using a disability studies framework of empowerment / Pamela Block, Eva L. Rodriguez, Maria C. Milazzo, William S. MacAllister, Lauren B. Krupp, Akemi Nishida, Nina Slota, Alyssa M. Broughton, Christopher B. Keys -- Communities of prosthesis users and possibilities for personal innovation / Cynthia E. Schairer -- Creating a village to raise a child : constructing community in families of children with disabilities / Sara E. Green, Julia Barnhill, Sherri Green, Diana Torres Hawken, Loretta Sue Humphrey, Scott Sanderson -- Crossing borders, pushing boundaries : disabled refugees' experiences of community and community participation in the USA / Mansha Mirza, Joy Hammel -- The quest for community : intellectual disability and the shifting meaning of community in activism / Allison C. Carey -- Same mandate, changing concepts of community : an analysis of bills to mandate Medicaid coverage of community-based attendant services and supports (1997-2010) / Brian R. Grossman -- The contested meaning of 'community' in discourses of deinstitutionalization and community living in the field of developmental disability / Liat Ben-Moshe -- Disability and the neoliberal Indian state : the perils of community participation / Vandana Chaudhry.
Keywords: Social Science -- People with Disabilities; Social Science -- Sociology -- General; Social Science -- General; Disability: social aspects; Sociology; Sociology of disability; People with disabilities -- Social conditions